GENDER DIFFERENCES IN PERSONAL CHARACTERISTICS AND JOB SATISFACTION OF FORESTRY RESEARCH INSTITUTE OF NIGERIA EMPLOYEES, NIGERIA - Olaoluwa Ayodeji ADEBAYO; Oluwakemi Enitan FAPOJUWO; Ebunlola OMOLE; Hafsah Laraba MOHAMMED; Deji JOSHUA; Jude CHIKEZIE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Individual job satisfaction enhancement alongside gender differences determination could lead to improvements and innovations which is often linked to organisational commitment, turnover intentions and absenteeism in the workplace. This study examined the gender differences and job satisfaction of the Forestry Research Institute of Nigeria employees, Nigeria. Multi-stage sampling procedure was used to select 226 (160 male and 66 female) employees in the study organisation. Primary data were obtained on respondents’ personal characteristics and job satisfaction through the use of a structured questionnaire. Job satisfaction was constructed around Herzberg’s motivation theory and measured through employee perceptions of extrinsic and intrinsic job characteristics. Percentages, means and Paired-Samples T-Test were used for data analysis. Results showed that the mean age of the employees, their household size, work experience and annual income were 40 years, 4 persons, 9 years and ₦1,272,635 respectively while 87.2% of them were married. The findings revealed that age (t = -3.53), household size (t = -2.83), income (t = -6.65), extrinsic (hygiene factor) motivation (t = 3.05) and job satisfaction (t = 1.81) significantly vary (p < 0.05) between female and male employees in the organisation. The study concluded that with respect to the gender status of the employees, the organisation should consider employees’ personal characteristics, motivation factors and job satisfaction attributes by the way they are derived to realize predictable positive organisational results as gender has to do with one’s enthusiasm and fulfilment.